The Growth, Feed Efficiency, and Survival Rate of Bonylip Barb (Osteochillus hasselti) in Biofloc Media C/N Ratio 10 with Different Stock Densities - Fia Sri Mumpuni; Muarif Muarif; Nani Yulianti; Aziz Mufadhdha hilmy (Journal of Aquaculture and Fish Health, 2022)
Bonylip barb (Osteochillus hasselti) is a favourite freshwater fish, especially in West Java, Indonesia.  Cultivation of bonylip barb is carried out in a conventional method; therefore, it is necessary to apply new cultivation technology, namely biofloc. The purpose of this study was to know the growth, feed efficiency, and survival rate of Bonylip barb in biofloc system cultivation (C/N ratio 10) with different stocking densities.  This research was conducted in March – July 2021, and the experiment was conducted at the Laboratory of Aquaculture, Faculty of Agriculture, Djuanda University, Bogor.  The object of research is bonylip barb seed (size 4.5 – 5.5 cm). The research design was a completely randomized design with three treatments of stocking density {A (10 fish/21 L), B (20 fish /21 L), and C (30 fish /21 L)} with four replications. Parameters observed were specific growth rate, feed efficiency, survival rate, and water quality. Furthermore, data were analyzed using analysis of variance (ANOVA) and LSD test.  The results showed that treatment A (stocking density 10 fish/21 L) had the best performance with a specific weight growth rate (2.03 ± 0.15%), feed efficiency (78.7%), and survival rate (100%). Water quality during the study was feasible for bonylip barb life. Keywords: Biofloc, Molasses, Osteochillus hasselti, Specific Growth Rate, Survival Rate